1986
DOI: 10.1002/mpo.2950140306
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biologic features predict poor prognosis in acute lymphoid leukemias in children and adolescents: A pediatric oncology group review

Abstract: Although the prognosis of children with ALL has improved markedly, approximately one-half of children continue to relapse. Clinical and biologic features of ALL have been studied at the time of diagnosis and many of these features have been shown to predict the risk of relapse, permitting tailoring of therapy based on relapse hazard. Results of studies of the Pediatric Oncology Group (POG) detailed here demonstrate that high white blood cell (WBC) count at diagnosis, very young or older age within childhood, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
2

Year Published

1987
1987
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 11 publications
4
31
0
2
Order By: Relevance
“…Addendum: exceptions that may prove the rule Infant acute leukaemias Infant (<18 months) acute leukaemias occur at a very low incidence rate but have a particularly poor prognosis (Crist et al, 1986;Pui et al, 1990). This may in part be explained by the difficulties of treating such young individuals but features of the leukaemic cell populations are also likely to be relevant.…”
Section: Implications For Therapymentioning
confidence: 99%
“…Addendum: exceptions that may prove the rule Infant acute leukaemias Infant (<18 months) acute leukaemias occur at a very low incidence rate but have a particularly poor prognosis (Crist et al, 1986;Pui et al, 1990). This may in part be explained by the difficulties of treating such young individuals but features of the leukaemic cell populations are also likely to be relevant.…”
Section: Implications For Therapymentioning
confidence: 99%
“…[1][2][3][4][5] The outcome for most of these children has improved with the use of intensive chemotherapy after the induction of remission, but approximately 30 percent of such high-risk patients eventually relapse. [5][6][7][8] Numerous studies have demonstrated that a rapid response to initial chemotherapy is an important prognostic factor in childhood ALL.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] ALL in infancy has several distinctive clinical characteristics compared with common childhood ALL, including hyperleukocytosis, hepatosplenomegaly, central nervous system (CNS) disease and a high frequency of molecularly evident rearrangement of the MLL gene at chromosome band 11q23. [9][10][11][12] Among these features, MLL gene rearrangement, found in 70-80% of infant ALL cases studied with molecular techniques, is an independent risk factor most predictive of recurrent leukemia. [13][14][15] The high failure rate in infants with ALL, especially those with MLL gene rearrangement, can be attributed to early relapse after remission rather than toxicity, and warrants consideration of intensified therapy.…”
Section: Introductionmentioning
confidence: 99%